Topical Treatment of Hair Loss with Formononetin by Modulating Apoptosis - Kim, Mi Hye; Choi, You Yeon; Lee, Ji Eun; Kim, Kyuseok; Yang, Woong Mo (Planta Medica, 2016)
Formononetin is one of the main components of red clover plants and its role on hair regrowth against hair loss has not been established yet. In the present study, we assessed the potential effects of formononetin on alopecia, along with impaired hair cycles by induction of apoptosis-regression.Depilated C57BL/6 mice were used for monitoring the hair cycles. Formononetin (1 and 100 µM) was topically treated to the dorsal skin for 14 days. Topical formononetin treatment induced miniaturized hair follicles to recover to normal sizes. Tapering hair shaft began to grow newly, emerging from the hair follicles by formononetin. In addition, formononetin inhibited the activation of caspase-8 and decreased the procaspase-9 expression. As a result of formononetin treatment, anti-apoptotic Bcl-2 was up-regulated, whereas pro-apoptotic Bax and p53 were down-regulated, resulting in a decrease of caspase-3 activation. Formononetin showed the obvious inhibition of apoptosis under terminal deoxynucleotidyl transferase dUTP nick end labeling staining thereafter.Taken together, our findings demonstrate that formononetin exerted the hair regrowth effect on hair loss, in which the underlying mechanisms were associated with Fas/Fas L-induced caspase activation, thus inhibiting apoptosis.
Keywords: formononetin; hair loss; hair cycle; apoptosis; caspase